Validity of The PTSD Symptoms Scale Self Report (PSS-SR) in Iran - Monireh-Sadat Mirzamani; Javad Mahmoudi-Gharaei; Mohammad Reza Mohammadi; Seyed-Mahmoud Mirzamani (Iranian Journal of Psychiatry, 2007)
Objective: Since1980, when Post-traumatic Stress Disorder (PTSD) was officially recognized as a unique diagnostic entity and was included in the Diagnostic and Statistical Manual-III, a large body of research has been done in the assessment of this disorder. This study investigated the applicability of the Persian form of the Post-traumatic Stress Disorder Symptom Scale Self Report (PSS-SR) in a group of Iranians who had been directly involved in a disaster in Iran (from May 4th 2002 to 20 April 2005).  Method: The participants were 109 individuals who had been directly involved in one of the three disasters which happened in Iran: A- 20 adolescents who survived the boat sinking or witnessed it in Tehran's city park on May 4th 2002; B- 50 persons who survived the Bam earthquake; C- 39 persons who survived the accident in Tehran's airport on April 20th 2005. The assessment measures used were the Post-traumatic Stress Disorder Symptom Scale Self Report (PSS-SR) and psychiatric interview based on DSM-IV-TR.  Results: 90 participants (81%) were diagnosed with PTSD using the PSS-SR and 93 (83.8%) were diagnosed with PTSD by psychiatric interview. Correlation coefficients between the PSS-SR and the psychiatric interviews were significant (r= .62, p< .001).  Conclusion: The PSS-SR appears to be an effective and efficient method of screening for PTSD.